Slavery: Annual bibliographical supplement (2004). - Thurston, Thomas; Miller, JosephC. (Slavery & Abolition, 2005)
The article presents the 2004 annual bibliographical supplement of "Slavery and Abolition" journal. Joseph C. Miller has worked on the development of this bibliography since 1977, with the assistance of many colleagues and the institutional support of the University of Virginia. The 2004 annual supplement is the first to be compiled by the Gilder Lehrman Center for the Study of Slavery, Resistance, and Abolition, at Yale University.